Fluorescence and Label Free Impedimetric DNA Detection on SnO2 Nanopillars. Issue 5 (24th March 2015) - Le, Minh Hai; Fradetal, Louis; Delabouglise, Didier; Mai, Anh Tuan; Stambouli, Valerie
Abstract SnO2 is a n‐type semiconductive oxide with attractive characteristics mainly based on easy elaboration and functionalization routes in addition to chemical robustness. We have fabricated SnO2 nanopillars based DNA sensor to perform the label free (without any redox compound) impedimetric DNA detection. The non faradaic electrochemical impedance spectroscopic (EIS) behavior and more particularly the evolution of the polarization resistance the SnO2 nanopillars has been thoroughly investigated upon the different steps of their functionalization process up to DNA hybridization. Similarly to our previous study on planar 2D SnO2 surfaces, the DNA hybridization induces a systematic increase of the polarization resistance, the magnitude of which decreases with the target DNA concentration. This DNA concentration dependence matches the one obtained from epifluorescence intensity measurements. A common value of DNA detection limit, i.e. 2 nM, is found from both measurement techniques. Interestingly the 3D view intensity obtained by confocal scanning laser fluorescence microscopy confirms that the DNA molecules are mainly grafted along the SnO2 nanopillars. Finally both impedance and fluorescence measurements obtained in the case of 1‐ and 2‐base mismatch hybridizations demonstrate the selectivity of the SnO2 nanopillars based DNA sensor. These preliminary results open the way to further investigations on the influence of both the shape ratio and electrical properties of the SnO2 nanopillars on the impedance variations related to DNA hybridization, notably in view of improving the sensor performances.